The Effect of Tax and Leverage on Transfer Pricing Decisions with Institutional Ownership as Moderating - Zahrotun Nisa; Wahidahwati Wahidahwati; Suwardi Bambang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of tax and leverage on transfer pricing decisions with institutional ownership as moderating. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique used is purposive sampling. The number of samples in this study amounted to 110 observations. This research is classified as quantitative research which is tested using the Moderating Regression Analysis (MRA) analysis technique. The results of this study indicate that taxes have a significant effect on transfer pricing decisions. Leverage has no significant effect on transfer pricing decisions. While the variable of institutional ownership as a moderating factor is not able to moderate the relationship of tax effect on transfer pricing decisions, but institutional ownership is able to moderate the relationship of leverage to transfer pricing decisions. The coefficient of determination is 0.138, which means that 13.8% of the indications that the company is doing transfer pricing is influenced by this variable, while the rest is explained by other variables. This shows that there are still many variables outside the study that can explain transfer pricing.